Dynamic Pricing Regulation and Welfare in Insurance Markets - Aizawa, Naoki; Ko, Ami (Journal of Political Economy, 2025)
While the traditional role of insurers is to provide protection against individuals? idiosyncratic risks, insurers themselves face substantial uncertainties due to aggregate shocks. To prevent insurers from passing these aggregate risks onto consumers, governments have increasingly adopted dynamic pricing regulations, which limit insurers? ability to change premiums over time. We evaluate dynamic pricing regulation using an equilibrium model of the US long-term care insurance market, featuring insurers? lack of commitment and endogenous market structures. We find that stricter dynamic pricing regulation has a limited impact on improving consumer welfare, while it reduces insurer profits and increases market concentration.